Pengaruh Suhu dan Waktu Pemblansiran terhadap Karakteristik Tepung Sukun - Aidil Fitriansyah; Sri Waluyo; Cicih Sugianti; Tamrin Tamrin (Jurnal Agricultural Biosystem Engineering, 2022)
The aims of this research were to determine the effect of temperature and duration of blanching to the characteristics of breadfruit flour and to test the level of consumer preference of cake made from breadfruit flour. Completely randomized factorial design with two factors: temperature (60°C, 70°C, 80°C) and duration of blanching (4 and 6 minutes) was conducted. The parameters measured are fineness modulus, grain size distribution, bulk density, color index and organoleptic score of cake made from breadfruit flour as a part or overall materials. The results showed that the temperature and blanching time affect the fineness modulus and of breadfruit flour granules. The higher the temperature, the longer the blanching time, and the smoother the fineness modulus, the finer the breadfruit flour granules. While, the lower the temperature and the duration of blanching, the color index of breadfruit flour is getting closer to white. The cakes made from 100% of breadfruit flour still have lower preference score compared with the cakes made from 100%  of wheat flour in terms of taste, aroma, texture and color. Keywords: Blanching, Breadfruit, Flour.